اُصولِ اِباحت پر مختلف نقطہ ہاےنظر کا تجزیاتی مطالعہ ------------------------------------------------------------------------------------- Principle of Permissibility in Various Connotations: An Analytical Study - احمد, حافظ آفتاب; الاسنادی, حافظ ظہیر احمد (FIKR-O NAZAR فکر ونظر, 2016)
An extensive and intensive study of the Holy Qur’an and Sunnah clarifies this fact that Islam has evidently allowed and forbidden certain things. Basic principles have already been prescribed in Islamic Shariah, however, there are several matters where the sources prefer to remain silent. In this research paper, an endeavor has been made to highlight the different standpoints regarding the Principle of Permissibility along with its lexical and technical meaning. Different schools of thought have presented their own understandings and their derived opinions have also been presented. This principle has been critically and analytically evaluated in the light of different connotations made by the scholars of Islam and finally the preferred viewpoint has been suggested. After a thorough investigation, we came to this conclusion that all those things which are not in the prohibited list of shariah are allowed and permissible.